Tingkat Kecanduan Smartphone dan Self Efficacy dengan Prestasi Belajar Mahasiswa Fakultas Kedokteran Universitas Malahayati - Beta Gustilawati; Deviani Utami; Supriyati Supriyati; Achmad Farich (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: The use of smartphones by students have positive and negative impacts on the learning process. The ease in obtaining information with smartphones makes students motivated to participate in the learning process in class. Learning achievement is influenced by characteristics that indicate the factors originating from within students, one of which is self-efficacy which refers to self-confidence in the abilities possessed. Methods: The design of this study was observational analytic with a cross-sectional design. The sampling technique in this study used a purposive sampling method and obtained a total sample of 118 people. Data analysis used the Spearman trial test. Research Results: The result of Spearman correlation bivariate statistical test obtained that each p-value = 0.024 in smartphone addiction and p-value = 0,000 in self-efficacy.Conclusion: There is a significant relationship between smartphone addiction and self-efficacy with learning achievement of the students in the Medical Faculty, University of Malahayati, class of 2018